What determines the elasticity of substitution between capital and labor? A literature review - Michael Knoblach; Fabian Stöckl (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper provides the first comprehensive review of the empirical and theoretical literature on the determinants of the elasticity of substitution between capital and labor. Our focus is on the two-input constant elasticity of substitution (CES) production function. By example of the U.S., we highlight the distinctive heterogeneity in empirical estimates of σ at both the aggregate and industrial level and discuss potential methodological explanations for this variation. The main part of this survey then focuses on the determinants of σ. We first review several approaches to the microfoundation of production functions, especially the CES production function. Second, we outline the construction of an aggregate elasticity of substitution (AES) in a multi-sectoral framework and investigate its dependence on underlying sectoral elasticities. Third, we discuss the influence of the institutional framework on the determination of σ. The concluding section of this review identifies a number of potential empirical and theoretical avenues for future research. Overall, we demonstrate that the effective elasticity of substitution (EES), which is typically estimated in empirical studies, is generally not an immutable deep parameter but depends on a multitude of technological, non-technological and institutional determinants.
Keywords: D24; E23; O14; O40; 330; elasticity of substitution; aggregate elasticity; capital; labor; economic growth; microfoundation; Cobb-Douglas and CES production function